Rethinking the reproduction and innovation of modernism in China through Kunio Maekawa’s residential district planning in Shanghai - Shuai, Shao (International Planning History Society Proceedings, 2024)
This paper investigates Kunio Maekawa's contributions to urban construction through two residential projects in Shanghai, initiated by different clients and yielding varied outcomes. The planning of the Oriental Development Company residential district showcased the designer's avant-garde understanding of modernist urban planning theory and reflected his aspirations for Shanghai's urban development at the time. The Hua-Hsing Commercial Bank residential district, which was successfully realized, demonstrated Maekawa's skill in adapting modernist principles to meet the local context and urban planning needs of Shanghai. The analysis focuses on the realized Hua-Hsing Commercial Bank residential district, exploring how Maekawa's designs fostered community interaction and social cohesion. The project underscored his innovative integration of public spaces within residential districts, which not only enhanced the residents' quality of life but also strengthened community bonds. These spaces were thoughtfully designed to balance high- density housing with accessible communal green areas, reflecting a sophisticated understanding of the interplay between architecture and urban living dynamics. By examining these projects, the paper highlights Maekawa's significant impact on urban development and modernist architecture in Asia, particularly through his thoughtful approach to designing community-oriented living spaces in rapidly expanding urban environments.